PACAP/VIP AND RECEPTOR CHARACTERIZATION IN MICTURITION PATHWAYS IN MICE WITH OVEREXPRESSION OF NGF IN UROTHELIUM - Girard, Beatrice M. (2010)
Urothelium-specific overexpression of NGF in the urinary bladder of transgenic mice stimulates neuronal sprouting or proliferation in the urinary bladder, produces urinary bladder hyperreflexia and results in increased referred somatic hypersensitivity. Additional NGF-mediated changes might contribute to the urinary bladder hyperreflexia and pelvic hypersensitivity observed in these transgenic mice such as upregulation of neuropeptide/receptor systems. Chronic overexpression of NGF in the urothelium was achieved through the use of a highly urothelium-specific, uroplakin II promoter. In the present study, we examined PACAP, VIP and associated receptors (PAC1, VPAC1, VPAC2) transcripts or protein expression in urothelium and detrusor smooth muscle and lumbosacral DRG in NGF-overexpressing and littermate wildtype mice using real-time quantitative reverse transcription-polymerase chain reaction and immunohistochemical approaches. Results demonstrate upregulation of PAC1 receptor transcript and PAC1-immunoreactivity in urothelium of NGF-OE mice whereas PACAP transcript and PACAP-immunoreactivity were decreased in urothelium of NGF-OE mice. In contrast, VPAC1 receptor transcript was decreased in both urothelium and detrusor smooth muscle of NGF-OE mice. VIP transcript expression and immunostaining was not altered in urinary bladder of NGF-OE mice. Changes in PACAP, VIP and associated receptors transcripts and protein expression in micturition pathways resemble some, but not all, changes observed after induction of urinary bladder inflammation known to involve NGF production.